The Legal Concept of Joint Property of Mixed Marriage in the International Civil Law System from the Perspective of Legal Justice - Khairunnisa, Fitri; Suhariningsih, Suhariningsih; kusumadara, Afifah; Widaqdo, Setyo (CV. AFDIFAL MAJU BERKAH, 2024)
Mixed marriage between Indonesian citizens and foreign citizens has become an increasingly common phenomenon due to rapid globalization and increasing tourist visits to Indonesia. One of the main issues is regarding the arrangement of joint property, which is influenced by the various legal systems of each couple's home country. This study aims to analyze the perspective of legal justice in the reform of joint property arrangements in mixed marriages. The research method uses a normative legal approach, with data collection through relevant literature reviews and in-depth interviews. The data was systematically analyzed and tested for validity using the triangulation method to ensure validity. The results of the study show that differences in legal systems between countries create significant challenges for couples in managing, owning, and dividing joint property. Inequality and discrimination are common, especially in cross-border property ownership, which can be detrimental to one party. To overcome this challenge, harmonization of international civil law is needed through the application of the principles of universal justice and inclusive legal reform. In addition, the development of marriage agreements that are responsive to globalization can be a solution to provide better legal protection, reduce uncertainty, and ensure that the rights of couples are met fairly. This study recommends legal reforms that prioritize the principles of justice and the protection of rights in mixed marriages, in order to create a legal system that is more responsive to the dynamics of globalization.